STRUKTUR KOMUNITAS IKAN INTRODUKSI DI DANAU BATUR, BALI [Community Structure of Introduced Fish in Lake Batur, Bali] - Sentosa, Agus Arifin; Wijaya, Danu (BERITA BIOLOGI, 2012)
Lake Batur is the largest lake in Bali island, however information on introduced fish community is not available yet. The research aimed to identify the community structure and ecological status of the introduced fish in Lake Batur, Bali. The study was carried out on May, July and October 2011 using survey method. The fishes were obtained using experimental gill nets and by fishermen. Data analysis included index of diversity, evenness, dominance, species richness and the abc (abundance-biomass comparison) curve. The results showed the tilapia (Oreochromis niloticus) was the dominant species. The status of introduced fish community suggested to ecological stress but it was relatively undisturbed.